Leis de escala no mapa padrão dissipativo - Vicente, Anderson Ricardo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Some dynamical properties for the dissipative standard map are studied. The map is described by two dynamical variables, namely 𝐼 and 𝜃 corresponding respectively to the action and angle variables. The model is characterized by two control parameters: (i) 𝜀 is responsible for controlling the nonlinearity of the system and; (ii) 𝛾 controlling the intensity of the dissipation of the system. For 𝛾 = 0 the results for the Taylor-Chirikov standard map are recovered. It means that for a non-dissipative case and, depending on the parameter 𝜀, the phase space of the system is mixed therefore showing periodic islands, invariant spanning curves and chaos. When 𝜀 > 𝜀𝑐 = 0,9716…, the invariant spanning curves are destroyed and the variable action can spread without limits over the phase space. When 𝛾 ≠ 0 the system is called dissipative; chaotic attractors appear in the phase space and there is a suppression of the unlimited dissemination of the variable action in the phase space. We investigate the dynamics of the standard map in the neighboring of two transitions: (i) local chaos to global chaos and; (ii) limited growth of action to unlimited growth of action. We show the behavior of the average quadratic actions (𝐼𝑅𝑀𝑆) determined by the critical exponents that characterize the dynamics near the transition of unlimited diffusion to limited diffusion of the variable action using two methods: (I) phenomenological and; (II) analytical

Estudamos algumas propriedades dinâmicas do mapa padrão dissipativo. O mapa é descrito por duas variáveis dinâmicas, 𝐼 e 𝜃, sendo elas ação e ângulo respectivamente. A dinâmica é caracterizada por dois parâmetros de controle, a saber, 𝜀 é responsável pelo controle da nãolinearidade do sistema e 𝛾 controla a intensidade de dissipação no sistema. Para 𝛾 = 0 os resultados para o mapa padrão de Taylor - Chirikov são recuperados. Dependendo do valor para 𝜀 o espaço de fases é misto exibindo ilhas de periodicidade, curvas invariantes do tipo spanning e caos. Quando 𝜀 > 𝜀𝑐, onde 𝜀𝑐 ≅ 0,9716…as curvas invariantes do tipo spanning são destruídas e a variável ação pode se difundir sem limites ao longo do espaço de fases. Para 𝛾 ≠ 0 o sistema é dito ser dissipativo. Atratores surgem no espaço de fases e ocorre uma supressão da difusão ilimitada da variável ação no espaço de fases. Neste trabalho investigamos a dinâmica do mapa padrão nas proximidades de duas transições: (i) caos local para caos global e; (ii) crescimento limitado da ação para crescimento ilimitado da ação. Mostramos o comportamento da ação quadrática média (𝐼𝑅𝑀𝑆) e determinamos os expoentes críticos que caracterizam a dinâmica próximo a transição de difusão limitada para ilimitada da variável ação empregando dois métodos: (I) fenomenológico e; (II) analítico
Keywords: Sistemas dinâmicos diferenciais; Caos determinístico; Transformações de fase (Física estatística); Leis de escala (Fisica estatistica)